Comparison of parallel group velocity of ECH waves with electron resonant velocity: Implication for electron diffusion by ECH waves - Tripathi A.K.; Singhal R.P. (My University, 2025)
We have investigated the role of group velocity in the calculation of pitch-angle diffusion coefficients by electron cyclotron harmonic (ECH) waves in planetary magnetospheres. The assumption which is generally made that the parallel group velocity can be neglected in comparison with particle parallel velocity is examined in detail. It is found that for lowest harmonic band this assumption is quite good. It is found that in general it is not possible to ignore the parallel group velocity. However, for lowest harmonic band this assumption is quite good at low electron temperatures. © 2009.